Post-digital rhetoric and the new aesthetic - Hodgson, Justin (New directions in rhetoric and materiality., 2019)
"Uses the New Aesthetic to argue we are not just in a 'post-human' moment but a 'post-digital' one, where the blurring between the 'real' and the 'digital' has fundamentally reconfigured how we make sense of the world"--